IMPROVING STUDENTS’ ABILITY IN WRITING NARRATIVE TEXT BY USING STORY MAP TECHNIQUE OF THE EIGHT GRADE STUDENTS AT MTsDDI KEL.BARU TOLITOLI - Inda Indrawati (Universitas Madako Tolitoli, 2019)
The objective of the research is to identify whether the use of story map technique can improve students’ ability in writing narrative text. This pre-experimental study uses 23 students as a sample. They are grade eight at MTs DDI Kel. BaruTolitoli. The procedure of this research consists of pretest, treatment, and posttest. The researcher gives pretest and posttest to know the use of story map technique can improve the students’ ability in writing narrative text or not. The result of the analysis shows that story map technique contributes greatly to the students in comprehending narrative text. It can be seen by the difference of the mean score between pre-test and post-test. The mean score of pre-test is 62.30 while in the post-test improve up to 82.09. The data of this research are analyzed by SPSS Program 16. Moreover, the Minimum Mastery Criterion of English lesson is 75 (seventy-five). Then the data of both test are analyze by using T-test, and the result show that the T-test value 7.572 is greater than T-table value 2.074. It can be inferred that story map technique is very effective to improve students’ ability in writing narrative text. Keywords: Improving, reading comprehension, narrative text, scanning technique. Bal, Mieke 2009. Narratology (introduction to the theory of narrative).Canada.Univerisity of Toronto press incorporated.Bushel Sharon. 2011. Writing a Narrative Paragraph. Available from: http://www.berniejones.com/lessonplans/36writingNarativeParagraph.htmCrystal David. 2008. A Dictionary of Linguistic and Phonetic. USA. Blackwell PublishingDodd, Ellen Nancy. 2011.The Writer’s Compass.UK. F&W Media International LTD.Haris, David P. 1969. Testing English as second language. New York. McGraw Hill inc.Harmer, Jeremy. 2004. How to Teach Writing. Edinburgh Gate: Pearson EducationHudak.C Heater. 2008. Narrative Paragraph. USA. Weigel Publisher Inc.Melly. 2006. All kinds of Writing (Writing description or Deskriptive Writing).USA. Blackwell Publishing.McDonough, J., and Shaw, C. (2003) Materials and Methods in ELT . 2nd ed. Maine : Blackwell Publishing.Saskatoon. 2011. Instructional Strategy Online. Available from: http://olc.spsd.sk.ca/de/pd/instr/strats/storymapping/index.html